First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Optical and radio characterization of continuing current lightning with ASIM, GLM and ELF sensors - P.A. Camino-Faillace; F.J. Gordillo-Vázquez; F.J. Pérez-Invernón; J. Montanyà; J. Młynarczyk; T. Neubert; O. Chanrion; N. Østgaard (Atmospheric Research, 2026)

Drifting fish aggregation devices as a tool to study oceanic marine protected areas - Arthur Blanluet; Edward T. Game; Kydd Pollock; Nicholas H. Wolff; Jason D. Everett; Sandra Neubert; Daniel C. Dunn; Anthony J. Richardson (Fisheries Research, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Employing optical lightning data to identify lightning flashes associated to terrestrial gamma-ray flashes - Christoph Köhn; Matthias Heumesser; Olivier Chanrion; Victor Reglero; Nikolai Østgaard; H. J. Christian; T. J. Lang; R. J. Blakeslee; Torsten Neubert (Bulletin of Atmospheric Science and Technology, 2024)
Terrestrial gamma-ray flashes (TGFs) are bursts of energetic X- and gamma-rays emitted from thunderstorms. The Atmosphere-Space Interactions Monitor (ASIM) mounted onto the International Space Station (ISS) is dedicated to measure TGFs and optical signatures of lightning; ISS LIS (Lightning Imaging Sensor) detects lightning flashes allowing for simultaneous measurements with ASIM. Whilst ASIM measures $$\sim $$ ∼ 300-400 TGFs per year, ISS LIS detects $$\sim 10^6$$ ∼ 10 6 annual lightning flashes giving a disproportion of four orders of magnitude. Based on the temporal evolution of lightning flashes and the spatial pattern of the constituing events, we present an algorithm to reduce the number of space-detected flashes potentially associated with TGFs by $$\sim $$ ∼ 60% and of associated LIS groups by $$\sim $$ ∼ 95%. We use ASIM measurements to confirm that the resulting flashes are indeed those associated with TGFs detected at approx. 400 km altitude and thus benchmark our algorithm preserving 70–80% of TGFs from concurrent ASIM-LIS measurements. We compare how the radiance, footprint size and the global distribution of lightning flashes of the reduced set relates to the average of all measured lightning flashes and do not observe any significant difference. Finally, we present a parameter study of our algorithm and discuss which parameters can be tweaked to maximize the reduction efficiency whilst keeping flashes associated to TGFs. In the future, this algorithm will hence be capable of facilitating the search for TGFs in a reduced set of lightning flashes measured from space.

Integrative phylogenetic, phylogeographic and morphological characterisation of the Unio crassus species complex reveals cryptic diversity with important conservation implications - M. Lopes-Lima; J. Geist; S. Egg; L. Beran; A. Bikashvili; B. Van Bocxlaer; A.E. Bogan; I.N. Bolotov; O.A. Chelpanovskaya; K. Douda; V. Fernandes; A. Gomes-dos-Santos; et al. (Molecular Phylogenetics and Evolution, 2024)

Prevalence of antibodies against hepatitis A virus among children and adolescents in Germany - A. Krumbholz; A. Neubert; H. Girschick; H. I. Huppertz; P. Kaiser; J. Liese; A. Streng; T. Niehues; J. Peters; A. Sauerbrey; H. Schroten; T. Tenenbaum; et al. (Medical Microbiology and Immunology, 2013)

Seven years of recent European net terrestrial carbon dioxide exchange constrained by atmospheric observations - W. PETERS; M. C. KROL; G. R. Van Der WERF; S. HOUWELING; C. D. JONES; J. HUGHES; K. SCHAEFER; K. A. MASARIE; A. R. JACOBSON; J. B. MILLER; C. H. CHO; M. RAMONET; et al. (Global Change Biology, 2010)
We present an estimate of net ecosystem exchange (NEE) of CO 2 in Europe for the years 2001–2007. It is derived with a data assimilation that uses a large set of atmospheric CO 2 mole fraction observations (∼70 000) to guide relatively simple descriptions of terrestrial and oceanic net exchange, while fossil fuel and fire emissions are prescribed. Weekly terrestrial sources and sinks are optimized (i.e., a flux inversion) for a set of 18 large ecosystems across Europe in which prescribed climate, weather, and surface characteristics introduce finer scale gradients. We find that the terrestrial biosphere in Europe absorbed a net average of −165 Tg C yr −1 over the period considered. This uptake is predominantly in non‐EU countries, and is found in the northern coniferous (−94 Tg C yr −1 ) and mixed forests (−30 Tg C yr −1 ) as well as the forest/field complexes of eastern Europe (−85 Tg C yr −1 ). An optimistic uncertainty estimate derived using three biosphere models suggests the uptake to be in a range of −122 to −258 Tg C yr −1 , while a more conservative estimate derived from the a‐posteriori covariance estimates is −165±437 Tg C yr −1 . Note, however, that uncertainties are hard to estimate given the nature of the system and are likely to be significantly larger than this. Interannual variability in NEE includes a reduction in uptake due to the 2003 drought followed by 3 years of more than average uptake. The largest anomaly of NEE occurred in 2005 concurrent with increased seasonal cycles of observed CO 2 . We speculate these changes to result from the strong negative phase of the North Atlantic Oscillation in 2005 that lead to favorable summer growth conditions, and altered horizontal and vertical mixing in the atmosphere. All our results are available through http://www.carbontracker.eu

Analysis of vaccine-virus-associated rabies cases in red foxes (Vulpes vulpes) after oral rabies vaccination campaigns in Germany and Austria - Thomas Müller; H.-J. Bätza; A. Beckert; C. Bunzenthal; J. H. Cox; C. M. Freuling; A. R. Fooks; J. Frost; L. Geue; A. Hoeflechner; D. Marston; A. Neubert; et al. (Archives of Virology, 2009)

Recent Results from Studies of Electric Discharges in the Mesosphere - T. Neubert; M. Rycroft; T. Farges; E. Blanc; O. Chanrion; E. Arnone; A. Odzimek; N. Arnold; C.-F. Enell; E. Turunen; T. Bösinger; Á. Mika; et al. (Surveys in Geophysics, 2008)

New insights into the structure and hydration of a stratum corneum lipid model membrane by neutron diffraction - M. A. Kiselev; N. Y. Ryabova; A. M. Balagurov; S. Dante; T. Hauss; J. Zbytovska; S. Wartewig; R. H. H. Neubert (European Biophysics Journal, 2005)

Body size and food web structure: testing the equiprobability assumption of the cascade model - M. G. Neubert; S. C. Blumenshine; D. E. Duplisea; T. Jonsson; B. Rashleigh (Oecologia, 2000)

Influence of 13-cis and all- trans retinoic acid on rat embryonic development in vitro: correlation with isomerisation and drug transfer to the embryo - S. Klug; J. Creech Kraft; E. Wildi; H. -J. Merker; T. V. N. Persaud; H. Nau; D. Neubert (Archives of Toxicology, 1989)

Embryotoxicity induced by alkylating agents: 1. Ethylmethanesulfonate as a teratogen in mice - T. Platzek; G. Bochert; W. Schneider; D. Neubert (Archives of Toxicology, 1982)